8‐4: An Improved Image Data Compensation Method for Circular Display. Issue 1 (29th May 2019) - Zhu, Jiang; Wu, Yu; Chen, Yinhung; Zhao, Bin; Liu, Linfeng
Abstract : In this work, an efficient method is proposed to improve the visual quality of circular display. The compensation coefficient of the pixels at arc edge is calculated by their distance from the center of the circle. Experimental results show that the jagged edges of circular display can be effectively reduced by the given method.